Learning attitudes in excellent and average university students - Bernardo GARGALLO LÓPEZ; Gonzalo ALMERICH CERVERÓ; Eloína GARCÍA FÉLIX; Miguel Ángel JIMÉNEZ RODRÍGUEZ (Ediciones Universidad de Salamanca, 2011)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> Normal 0 21 false false false ES X-NONE X-NONE <![endif]--><!--[if gte mso 9]> <w:LsdException Locked="false" Priority="67" SemiHidden="false" U